Pharmacokinetics of diltiazem hydrochloride delay-onset sustained-release pellet capsules in healthy volunteers - Xi-Qing Yan; Zhi-Gang Chen; Rong-Liang Wang; Jun Yang; Fang Ai; Yan-Juan Pan; Pei-Yong Qiu; Da-Xin Wang (Brazilian Journal of Pharmaceutical Sciences, 2013)
The pharmacokinetics (PK) of ordinary tablets and sustained release capsules of diltiazem hydrochloride in human clinical trials had been studied. The PK of diltiazem hydrochloride delay-onset sustained-release pellet capsules, a new dosage form, has not been reported, although it is very important to clinical use. In this paper, we investigated the PK of diltiazem hydrochloride delay-onset sustained-release pellet capsules and the food influence in Chinese healthy volunteers. The PK parameters indicated that the diltiazem hydrochloride delay-onset sustained-release pellet capsules appeared marked characteristics of delayed and controlled release. An opened-label, randomized and parallel clinical trial was conducted in 36 Chinese healthy volunteers with single oral dose (90 mg, 180 mg or 270 mg) and a multiple oral dose (90 mg d-1×6 d) administration. The effect of food on the PK of one single oral dose (360 mg) was investigated in 24 healthy Chinese volunteers. Plasma diltiazem concentration was determined by reversed-phase high-performance liquid chromatography (RP-HPLC) and the main pharmacokinetic parameters were analyzed by PKSolver (Ver 2.0). All clinical studies were conducted in the Clinical Pharmacological Center (No. JDX1999064) of Xiangya Hospital Affiliated Central South University, China. The PK parameters suggested that the new formulation had marked characteristics of delayed and controlled release of diltiazem, and food intake did not alter significantly diltiazem pharmacokinetic parameters. Embora a farmacocinética (PK) do cloridrato de diltiazem nas formas de comprimidos de liberação imediata e cápsulas de liberação modificada em ensaios clínicos já tenha sido relatada, a pesquisa da PK do cloridrato de diltiazem na forma de cápsulas com peletes de liberação retardada e sustentada ainda é muito importante. Neste trabalho, propusemos avaliar a farmacocinética do cloridrato de diltiazem administrado através desta nova forma farmacêutica em voluntários chineses sadios, assim como a influência da ingestão de alimentos neste perfil farmacocinético. Foi realizado um ensaio clínico aberto, randomizado e paralelo em 36 voluntários, que receberam dose oral única de 90 mg, 180 mg ou 270 mg e dose múltiplas (90 mg/d × 6 d) pela mesma via de administração. Para avaliar o efeito da ingestão de alimentos sobre a PK do diltiazem foi realizada a administração de dose única (360 mg) em 24 voluntários chineses sadios. A concentração plasmática do diltiazem foi determinada por Cromatografia Liquida de Alta Eficiência em fase reversa (CLAE-FR) e os principais parâmetros farmacocinéticos foram analisados através do emprego do software PKSolver (Ver 2.0). O ensaio de farmacocinética clínica foi conduzido na clínica Pharmacological Center (No.JDX1999064) do Hospital de Xiangya, Central South University, China. Os parâmetros PK obtidos indicaram que a nova formulação de cápsulas de liberação retardada e sustentada de cloridrato de diltiazem possue marcantes características de liberação retardada e controlada do fármaco.